Value of Area Postrema Syndrome in Differentiating Adults With AQP4 vs. MOG Antibodies - Hyun, Jae-Won; Kwon, Young Nam; Kim, Sung-Min; Lee, Hye Lim; Jeong, Woo Kyo; Lee, Hye Jung; Kim, Byoung Joon; Kim, Seung Woo; Shin, Ha Young; Shin, Hyun-June; Oh, Sun-Young; Huh, So-Young; et al. (Frontiers in Neurology, 2020)
Objectives: To compare the frequency of area postrema syndrome (APS) in adults with anti-aquaporin-4 (AQP4) and anti-myelin oligodendrocyte glycoprotein (MOG) antibodies. Methods: APS is defined as acute or subacute, single or combined, episodic or constant nausea, vomiting, or hiccups, persisting for at least 48 hours, which cannot be attributed to any other etiology. The presence of APS was investigated in 274 adults with AQP4 antibodies and 107 adults with MOG antibodies from 10 hospitals. Results: The study population comprised Korean adults (≥18 years). At the time of disease onset, 14.9% (41/274) adults with AQP4 antibodies had APS, while none of the participants with MOG antibodies developed APS (p < 0.001). During the course of the disease, 17.2% (47/274) adults with AQP4 antibodies had APS in contrast to 1.9% (2/107) adults with MOG antibodies with APS (p < 0.001). Conclusions: APS, one of the core clinical characteristics of individuals with AQP4 antibodies, is an extremely rare manifestation in Korean adults with MOG antibodies.